2014
DOI: 10.1103/physrevd.90.103006
|View full text |Cite
|
Sign up to set email alerts
|

Rotating Ayón-Beato-García black hole as a particle accelerator

Abstract: We study the collision of two particles with equal masses moving in the equatorial plane near horizon of the rotating regular Ayón-Beato-García (ABG) black hole (BH) and calculate the centerof-mass (CM) energy for the colliding particles for both extremal and non-extremal cases. It turns out that CM energy depends not only on rotation parameter a but also on charge Q. Particularly for the extremal rotating regular ABG BH, CM energy of two colliding particles could be arbitrarily high for critical angular momen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
32
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 39 publications
0
32
0
Order By: Relevance
“…This gave an opening to explore ultrahigh energy collisions and astrophysical phenomena, such as gamma ray bursts and active galactic nuclei. Hence, the BSW mechanism received significant attention in the study of the collision of two particles near a rotating black hole [20,27,[31][32][33][34][35][36][37] (see also [38] for a review). In this section, we want to study the properties of E CM as r tends to the event horizon r + H in the case of a rotating Bardeen regular black hole.…”
Section: Near Horizon Collision In the Rotating Bardeen Regular Blackmentioning
confidence: 99%
“…This gave an opening to explore ultrahigh energy collisions and astrophysical phenomena, such as gamma ray bursts and active galactic nuclei. Hence, the BSW mechanism received significant attention in the study of the collision of two particles near a rotating black hole [20,27,[31][32][33][34][35][36][37] (see also [38] for a review). In this section, we want to study the properties of E CM as r tends to the event horizon r + H in the case of a rotating Bardeen regular black hole.…”
Section: Near Horizon Collision In the Rotating Bardeen Regular Blackmentioning
confidence: 99%
“…This prompted a generalization of these regular solutions to the axially symmetric case or to the Kerr-like solution [25][26][27][28][29], via the Newman-Janis algorithm [30] and by other, similar techniques [31][32][33]. It is also demonstrated that these rotating regular solutions can act as particle accelerator [34,35]. The algorithm also allowed one to generate a noncommutative inspired rotating black hole with a regular de Sitter toroidal region [36].…”
mentioning
confidence: 99%
“…Further, these regular black holes are very important as astrophysical black holes, like Cygnus X-1, although suppose to be like the Kerr black hole [32,33], but the actual nature of astrophysical black hole still need to be tested [32,33], and they may deviate from the Kerr black hole. More recently, the BSW mechanism when applied to an extremal regular black holes [34,35], also lead to divergence of the E CM . The main purpose of this paper is to study the collision of two particles with equal rest masses in the background of the rotating Hayward's regular black hole and to see what effect the deviation parameter g makes on the E CM .…”
Section: Jhep07(2015)015mentioning
confidence: 99%